Gastric side effects and the stomach dosimetric analysis in left-sided breast cancer radiotherapy in free-breathing and deep inspiration breath-hold technique - Dong Yang; Ying Piao; Fengshun Yuan; Hongtao Chen; Ding Zhang; Xianming Li (Radiation Oncology, 2022)
Abstract Background Adjuvant radiotherapy following surgery reduces the local recurrence and improves the prognosis. However, a considerable part of patients developed digestive reaction in daily treatment. In order to explore the correlation between breast radiotherapy and gastric toxicity, we investigated the clinic symptoms and stomach dose during DIBH or FB mode while left-sided breast cancer patients (LSBCP) receiving radiotherapy. Methods In the study, 124 LSBCP received adjuvant radiotherapy after surgery at our department were analyzed clinical characteristics and enquired about gastrointestinal side effects after treatment. Moreover, dosimetric parameters were assessed. Results There was no statistically significant difference between the two groups in age, T staging, N staging, hormone receptors, human epidermal receptor-2 (HER2), surgical methods, fractionated regimen, and chemotherapy conditions. However, larger stomach volumes and higher fractionated dose (Dmax/F) were associated with a statistically significantly greater risk for acute radiotherapy toxicity. In addition, the use of the DIBH gating technique (FB/DIBH) reduced the incidence of digestive reactions. Conclusion In order to cut down gastric side effects after breast radiotherapy, large meals should be avoided before treatment. DIBH treatment should be implemented in centers where conditions are satisfied to reduce radiotherapy side effects. Furthermore, dose limitation in stomach should be considered when the radiotherapy plan was formulated, especially for the patients treated with hypofractionated radiotherapy.